Factors Influencing the Integration of Building Information Modeling in Industrialized Building System Projects - Logendiran, Chitrarasan; Abdul Rahim, Nur Soleha; Ibrahim, Fazdliel Aswad (Advanced and Sustainable Technologies (ASET), 2026)
This paper examines the factors influencing the integration of Building Information Modeling (BIM) into Industrialized Building System (IBS) projects to understand current BIM integration practices among construction players, particularly IBS contractors in Wilayah Persekutuan Kuala Lumpur (WPKL) and Selangor. It aims to explore the criteria for technological adaptation and evaluate the level of technological adaptation for BIM-IBS implementation. Consequently, a literature review and instruments to conduct a mixed-methods approach were prepared to collect all required information. Subsequently, a qualitative analysis of the data was conducted. The findings indicate that financial factors consistently drive the most significant adaptation of BIM-IBS technology. The scores show a strong belief that technical abilities and workforce readiness are necessary to align with the demands of BIM-IBS (technical and individual around 4.0 with minimal variability), while financial and organizational perspectives are elevated but erratic (0.57–0.65), underscoring problems with governance and budgeting. In conclusion, experienced professionals are better equipped for and more likely to embrace BIM-IBS adaptation. The results show that the financial and organizational structures possess a strong foundation, both in structure and employee mindset, for effectively embracing new technologies, which aligns with SDG 9 Industry, Innovation, and Infrastructure.